Indeed money (gold) grows on trees - Shamsul Harumain, Zakuan Azizi; Keng, Shawn (Malaysian Biotechnology Information Centre (MABIC), 2019)
Recent Kim Kim River toxic pollution incident has raised eyebrows and sparked anger of Malaysian public about the irresponsible act of water pollution. Although this is an extreme pollution case of toxic proportion, day-to-day mining activities will leave behind mine wastes which may contain toxic chemicals such as arsenic that might be leached out during the refining process. Scientists are now using plants to remediate this hidden threat, and literally turning mine tailings into gold nanoparticles for industrial use. The Petri Dish (PD), guest writer, SHAWN KENG interviewed International Islamic University Malaysia’s Dr Zakuan Azizi Shamsul Harumain (ZA) – to explain what phytomining and phytoremediation are, and its promising “Midas Touch” potential in turning mine tailings into mine treasures.